Development of a Screening Tool to Estimate Vitamin A Intake and Comparison with Detailed Dietary Assessment Methods. (29th May 2020) - Engle-Stone, Reina; Miller, Jody; Stormer, Ame; Reario, Dolly; Capanzana, Mario; Cabanilla, Carl; Ford, Jennifer; Lietz, Georg; Haskell, Marjorie
Abstract: Objectives: We aimed to develop and validate a tool to estimate vitamin A (VA) intake and identify children at risk of intake above the tolerable upper intake level (UL). Methods: We developed, pilot-tested, and refined a screening tool to estimate VA intake among Filipino children 12–18 mo of age. Data were entered into tablets with pre-loaded food composition data to calculate VA intake immediately. The screening tool was used to identify children likely to have "adequate" (one group: 200–500 µg retinol activity equivalents, RAE/d) or "high" (two groups: >600 µg retinol/d) intake. Interviewers administered four 24-h recalls, one 12-h observed weighed record with 12-h recall, and a 30-d supplement questionnaire. Breastmilk intake and VA concentration were measured among breastfeeding children. We compared the screening tool and detailed dietary assessment (DDA) results for primary VA sources, group mean usual intake, and prevalence of intakes above the UL. Results: Major VA sources were similar between methods: fortified milk powders, multivitamin supplements, and breastmilk; contributions from intervention programs (e.g., micronutrient powders, fortified staple foods) were low. Mean usual retinol intakes for the high groups (n = 47 and 39, respectively) were 1218 and 1313 µg/d by screening tool vs. 1096 and 931 by DDA; 70 and 77% had usual intake above 600 µg/d. In the adequate group (n = 37), mean total VA intake was 375 and 559 µg RAE/d by screening and DDA, respectively. Conclusions: This screening tool provides a reasonably good rapid estimate of VA intake among Filipino children and can be useful for identifying groups with adequate to excessive intakes. Funding Sources: Bill & Melinda Gates Foundation.